Chronic Distress in Male Mice Impairs Motivation Compromising Both Effort and Reward Processing With Altered Anterior Insular Cortex and Basolateral Amygdala Neural Activation - Cabeza, Lidia; Ramadan, Bahrie; Cramoisy, Stephanie; Houdayer, Christophe; Haffen, Emmanuel; Risold, Pierre-Yves; Fellmann, Dominique; Peterschmitt, Yvan (Frontiers in Behavioral Neuroscience, 2021)
In humans and mammals, effort-based decision-making for monetary or food rewards paradigms contributes to the study of adaptive goal-directed behaviours acquired through reinforcement learning. Chronic distress modelled by repeated exposure to glucocorticoids in rodents induces suboptimal decision-making under uncertainty by impinging on instrumental acquisition and prompting negative valence behaviours. In order to further disentangle the motivational tenets of adaptive decision-making, this study addressed the consequences of enduring distress on relevant effort and reward-processing dimensions. Experimentally, appetitive and consummatory components of motivation were evaluated in adult C57BL/6JRj male mice experiencing chronic distress induced by oral corticosterone (CORT), using multiple complementary discrete behavioural tests. Behavioural data (from novelty suppressed feeding, operant effort-based choice, free feeding, and sucrose preference tasks) collectively show that behavioural initiation, effort allocation, and hedonic appreciation and valuation are altered in mice exposed to several weeks of oral CORT treatment. Additionally, data analysis from FosB immunohistochemical processing of postmortem brain samples highlights CORT-dependent dampening of neural activation in the anterior insular cortex (aIC) and basolateral amygdala (BLA), key telencephalic brain regions involved in appetitive and consummatory motivational processing. Combined, these results suggest that chronic distress-induced irregular aIC and BLA neural activations with reduced effort production and attenuated reward value processing during reinforcement-based instrumental learning could result in maladaptive decision-making under uncertainty. The current study further illustrates how effort and reward processing contribute to adjust the motivational threshold triggering goal-directed behaviours in versatile environments.